Judaism: the basics - Neusner, Jacob (Routledge, 2006)
Defining Judaism through stories -- Who and what is Israel? -- The community of Judaism and Passover -- The Israelite before God and the Days of Awe -- The individual Israelite and Israel in history : the Huppah, the covenant of Abraham; eating lunch -- The purpose of the law, the Ten Commandments, the Sabbath -- God is one, merciful and just -- The formation of normative Judaism -- The articulation of normative Judaism -- Reform, Orthodox, and Conservative Judaisms, Zionism -- How Judaism speaks today